Uncovering perspectives on physical activity in nursing homes: a qualitative exploration of the experiences of healthcare professionals and family caregivers - Stine Øverengen Trollebø; Kristin Taraldsen; Jonas Saur Heiland; Helen Hawley-Hague; Ellen Marie Bardal; Nina Skjaeret-Maroni (BMC, 2024)
Abstract Background The ageing population has increased the demand for healthcare services. In Norway, community-based long-term care are prioritised, leading to fewer nursing home places. As a result, nursing home residents are now older and have more complex needs. Nearly 92% of nursing home residents are affected by cognitive impairments accompanied by neuropsychiatric symptoms (NPS) that affect their daily activity, physical function, cognition, and behaviour. Traditionally, pharmacological therapy has been the prevailing treatment for NPS. However, emerging evidence suggests that physical activity can serve as an alternative treatment approach. Physical activity has the potential to maintain physical independence and enhance the quality of life (QoL) for the residents. Despite these benefits, institutionalisation in a nursing home often restricts activity levels of residents. This study explores facilitators and barriers to physical activity in nursing homes through the experiences of healthcare professionals and family caregivers. The goal is to enhance our understanding of how to promote and support physical activity for nursing home residents by identifying essential factors for successfully implementing daily physical activity initiatives. Methods Seven focus groups were conducted with a total of 31 participants. Participants included healthcare professionals (physiotherapists, nurses, unit- and department managers, assistant occupational therapists, and assistant nurses) and family caregivers of residents at nursing homes. Data were analysed using Braun and Clarke's reflexive thematic analysis, underpinned by hermeneutic phenomenology. Results Three main themes related to facilitators and barriers to physical activity in nursing homes were identified: inconsistency in task prioritisation; need for improved interprofessional collaboration; and need for improved utilisation of external resources. The participants experienced task prioritisation and lack of interdisciplinary collaboration as barriers to physical activity. The involvement of external societal resources was considered as both a facilitator and a necessity for obtaining physical activity in nursing homes. Conclusions This study highlights the need for a consensus in task prioritisation, enhanced competence among healthcare professionals, and better interdisciplinary collaboration to facilitate physical activity in nursing homes. Involving external societal resources could be a strategic approach to address barriers and support physical activity initiatives. Future research should focus on developing effective strategies for interdisciplinary collaboration that prioritises and promotes physical activity in nursing homes.